Unveiling Factors Affecting Audit Fees: Characteristics Of Firms And Public Accounting Firms - Saputra, Irwan Adimas Ganda; Hakim, Luqman; Wahjudi, Eko; Pratiwi, Vivi; Triani, Ni Nyoman Alit (JAS (Jurnal Akuntansi Syariah), 2024)
This study examines the effect of leverage, firm size, profitability, audit firm size, and audit tenure on audit fees. Using quantitative analysis, cross-sectional data from 281 companies listed on the IDX in 2022 were analyzed through purposive sampling and multiple linear regressions. The results show that firm size and audit firm size positively impact audit fees. Due to their operational complexity and higher audit risks, more prominent firms tend to incur higher fees as they require more detailed audit procedures. Similarly, firms audited by more prominent audit firms pay higher fees, as they are known for their strong reputation and ability to provide comprehensive, high-quality audit services, enhancing the credibility of the financial statements. However, leverage, profitability, and audit tenure do not affect audit fees. Theoretically, this study contributes to the audit fee literature by confirming the significant role of firm characteristics and audit firm size in determining audit costs. Practically, the findings offer insights for companies to strategically manage their audit fees by considering these factors, allowing them to maintain financial statement reliability while potentially optimizing audit costs. This balance is critical for firms seeking to manage resources efficiently without compromising the quality of their financial reporting